Pediatric Ethics Guidelines for Hereditary Medullary Thyroid Cancer - Rosenthal, MSara (BioMed Central, 2011)
Hereditary medullary thyroid cancer is an aggressive cancer for which there is no standard effective systemic therapy, but which can be prevented through genetic screening and prophylactic thyroidectomy. Although this cancer accounts for roughly 17% of all pediatric thyroid cancers, a significant percentage of affected families do not "accept" screening, while many gene carriers delay or refuse prophylactic thyroid surgery for their children. Current genetic screening practices in medullary thyroid cancer are inadequate; more than 50% of index patients with hereditary medullary thyroid cancer present with a thyroid mass; up to 75% have distant metastasis. These proposed pediatric ethics guidelines focus on two ethical issues that affect at-risk children: (1) how do we identify at-risk children whose RET-positive relative refuses to disclose that they carry the mutation? (2) How do we protect RET-positive children whose parents refuse prophylactic thyroidectomy?